Meningkatkan Pemahaman Puisi pada Siswa Kelas IV SD: Sebuah Studi Eksperimental tentang Metode SQ4R dengan Dukungan E-Book - Damayanti, Nisa Astari; Djuanda, Dadan; Karlina, Dety Amelia (Jurnal Bahasa dan Sastra, 2024)
Low comprehension of poetry texts among students is a significant educational challenge. It is characterized by difficulties in interpreting content and answering related questions. Monotonous teaching methods that fail to engage students or provide opportunities for deep exploration of poetic texts often cause this issue. If left unaddressed, this problem can hinder learning goals. The purpose of this study was to examine the impact of the Survey, Question, Read, Recite, Reflect, Review (SQ4R) method, assisted by e-book media, on improving poetry text comprehension in fourth-grade students. A quantitative, pre-experimental approach using a One-Group Pretest-Posttest design was employed. The entire population of 30 fourth-grade students was sampled through saturated sampling. Data were collected through pre- and post-tests and analyzed using a paired-samples t-test. The results showed a significant improvement in poetry comprehension, supporting the alternative hypothesis. The N-Gain analysis revealed a moderate level of improvement. Despite the modest gain, these findings suggest that the SQ4R method, when combined with e-book media, can significantly enhance students' poetry comprehension skills. This approach offers a more engaging and effective learning strategy compared to traditional methods. Future research should investigate the long-term effects of this method and its applicability across different age groups and literary genres. These results provide valuable insights for educators looking to diversify their teaching methods in reading comprehension instruction.